IMPLEMENTASI SADD AL-DZARI’AH DALAM AKAD MUAMALAH - Muhajirin Muhajirin (Balai Diklat Keagamaan Bandung, 2020)
Understanding the concept of Sadd al-Dzariah as a whole is a necessity owned by Islamic law researchers and fuqaha to establish the status of a law which develops in the community, and the issues of jurisprudence fiqh throughout these changing times, in particular. This study result is to refute the assumption of Imam ibn Hazm who rejected Sadd al-Dzariah as one of law devices or evidence to establish the law. He considered that Sadd al-Dzariah is a form of ijtihad using ratio approach and cannot be used as hujjah, as it departs from the assumption or presumption; not a belief, let alone Nash. The thing that should be understood in the concept of Sadd al-Dzariah in the context of Islamic law is the maintenance effort to all orders and prohibitions, and not to add provisions established in Syara'.Keywords: Sadd al-Dzariah; Islamic law; Hujjah